Indigenous practices of Traditional Health Practioners (THPs) methods by mothers of children admitted to the Polokwane/Mankweng hospital complex, Limpopo Province, South Africa - Bopape, M. A.; Mothiba T. A.; Malema, R. N. (My University, 2013)
The purpose of this study was to explore and describe the indigenous practices of mothers of children admitted to the paediatric unit of a Polokwane/Mankweng hospital complex in Limpopo Province, South Africa. An exploratory qualitative, phenomenological, descriptive research was conducted to explore and describe the indigenous practices of Traditional Health Practitioners (THPs) methods on children admitted in the paediatric unit of a Polokwane/Mankweng hospital complex in Limpopo Province. A non-probability purposive sampling method was used to select fifteen mothers of children admitted in the paediatric unit. Data were collected using unstructured one-to-one interviews. Data were analyzed using Tech’s open coding approach and three themes emerged namely; Analogous indigenous practices by THPs in curing childhood illnesses, beliefs related to the indigenous healing processes and THPs preventing spread of HIV infection to children. Health care providers should have an understanding of indigenous belief systems in relation to health; the government should advocate for the preservation of indigenous health practices and strengthen health education of community members and THPs with regard to the precautions to be taken when caring for HIV infected children.
Article published in: African Journal for Physical, Health Education, Recreation and Dance (AJPHERD), March 2013 (Supplement 1), pp. 147-158.
Keywords: Indigenous knowledge; Childhood illnesses; Traditional health practitioners; Children diseases -- South Africa; Healers -- South africa; Medicine, primitive -- South Africa; Traditional ecological knowledge